ECONOMIC AND SOCIAL IMPACT OF COVID-19 IN PERU - Huaman Fernandez, Jackeline Roxana (2021)
COVID-19 is a disease that has not only caused the loss of many human lives, but has also increased the poverty gap, impacting human development. Based on the above, the objective of this research was to identify the economic and social impact of the crisis caused by COVID-19 in Peru. The research was descriptive-explanatory and quantitative, and the design was non-experimental and cross-sectional. The unit of analysis consisted of documents referring to macroeconomic indicators of the States at the global level; in particular, documents detailing macroeconomic indicators at the national level, such as data from the Lima Stock Exchange and projections from the Ministry of Economy and Finance. In terms of data collection techniques and instruments, documentary analysis and the registration form were used, respectively. It was found that, between 2016 and 2019, a sustained growth rate was evidenced at the national level; however, the stoppage of economic activities to prevent the spread of COVID-19, led to a decrease in economic sectors. Based on the above, it was concluded that the sanitary crisis generated by COVID-19 has affected the development of Peru, increasing the levels of poverty and inequality, problems that will only be solved through the development and implementation of public policies that promote the adequate recovery of the national economy.